Immobilization of Lead from Pb-Contaminated Soil Amended with Peat Moss - Seul-Ji Lee; Myoung-Eun Lee; Jae Woo Chung; Jin Hee Park; Keun Young Huh; Gee-Ill Jun (Journal of Chemistry)
Immobilization of lead (Pb) using soil amendments can reduce Pb toxicity and bioavailability in soil. This study evaluated Pb immobilization in a Pb-contaminated soil by using peat moss through various tests. The Pb-contaminated soil (2000 mg Pb·kg−1) was amended with 1%, 5%, and 10% of peat moss to immobilize Pb in the soil. The immobilization properties of Pb in the contaminated soil were evaluated by a column leaching experiment, a microcosm test, and a batch incubation test. Peat moss significantly reduced the Pb leaching in all of the experiments and more effectively reduced mobility and toxicity of Pb in the column leaching and microcosm tests than bioavailability in the batch incubation test. The immobilized lead from the soils amended with 1%, 5%, and 10% of peat moss was 37.9%, 87.1%, and 95.4% from the column leaching test, 18.5%, 90.9%, and 96.4% from the microcosm test, and 2.0%, 36.9%, and 57.9% from the NH4NO3 extraction method, respectively, indicating that peat moss can be effectively used for the remediation of Pb-contaminated soil.